(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Adsorption and desorption are important processes that affect the distribution of chemicals in the environment. This research aims to determine the change pattern of PO42- concentration by time through adsorption and desorption simulations. The simulation process was conducted on sediments from Semarang and Jepara waters. Through the analysis of desorption process, the contribution of sediment input to the P ion can be determined, based on the release of ions PO42- at the beginning of time until the maximum conditions of the desorption process. The first and second order of (what) equations were used to determine the adsorption kinetics, while the isotherms of the adsorptions were determined based on the Langmuir and Freundlich models. The results show that the significant desorption process occurs during the first hour and the contribution of PO42- ions by Semarang sediments are three times higher than Jepara sediments. Based on the adsorption kinetics and isotherms, the second order of the equation model and the Langmuir model are more appropriate for both locations. This model assumes that the adsorption capacity is proportional to the number of active sites occupied by PO42- ions and the adsorption occurs in one homogeneous sedimentary layer. Semarang sediments have adsorp pollutants (P ions) ability greater than Jepara Sediments with capacity values respectively are 11.57 and 11.2 µmol g-1.